Pengembangan IoT Untuk Kendali AC Dengan Telegram Dan Sensor PIR - Atssabit, Muhammad Amru (JATISI, 2025)
Abstract The use of Internet of Things (IoT) devices is increasingly widespread in various fields, including air conditioning (AC) systems. This research aims to develop an IOT that allows users to remotely control Daikin air conditioners using Telegram on the NodeMCU ESP8266 platform, as well as integrate Passive Infrared (PIR) sensors to detect the presence of users. The system is designed to improve energy efficiency. This methodology involves IoT programming using microcontrollers, setting up communication with Telegram, and utilizing PIR sensors for motion detection. The test results show that the system can control the air conditioner via Telegram, provide notifications and allow commands to turn on and off the air conditioner based on the presence of the user detected by the PIR sensor. This implementation can increase the flexibility of air conditioning management, as well as provide comfort for users. In addition, this study also explores technical challenges such as the stability of the internet connection, system responsiveness, and ensuring that this system functions optimally. The results of this research are expected to contribute to the wider use of IoT technology in the field of household electronic device management.